Complex adaptive therapeutic strategy (CATS) for cancer - Cho, Yong Woo; Kim, Sang Yoon; Kwon, Ick Chan; Kim, In-San (ELSEVIER, 2014)
Tumors begin with a single cell, but as each tumor grows and evolves, it becomes a wide collection of clones that display remarkable heterogeneity in phenotypic features, which has posed a big challenge to current targeted anticancer therapy. Intra-and inter-tumoral heterogeneity is attributable in part to genetic mutations but also to adaptation and evolution of tumors to heterogeneity in tumor microenvironments. If tumors are viewed not only as a disease but also as a complex adaptive system(CAS), tumors should be treated as such and a more systemic approach is needed. Some of many tumors therapeutic strategies are discussed here from a view of a tumor as CAS, which can be collectively called a complex adaptive therapeutic strategy (CATS). The central theme of CATS is based on three intermediate concepts: i) disruption of artifacts, ii) disruption of connections, and iii) reprogramming of cancer-immune dynamics. Each strategy presented here is a piece of the puzzle for CATS. Although each piece by itself may be neither novel nor profound, an assembled puzzle could be a novel and innovative cancer therapeutic strategy. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: DRUG; HETEROGENEITY; PENETRATION; ULTRASOUND; EFFICACY; DELIVERY